Compressive behaviour of polyethylene terephthalate (PET) as partial coarse aggregate replacement in concrete - Poon, Siew Voon (2015)
In this developing world, the waste generated is gradually increased due to urbanization. Nevertheless, the solid waste in Malaysia is managed or disposed through landfill and partly to recycle. There is 35568 tons of waste being produced per day in Malaysia with the growth rate of 3.59% per year. In this rate of waste generation, the insufficient of landfill can become a significant problem in coming years. Therefore, recycle of solid waste is a compulsory act to prevent further destroying of environment and preserve the natural resources for the use of future generation. Waste accumulation can be solved by alternative solution such as replacement of aggregate by solid waste. The aim of this work is to determine performance of different percentage of Polyethylene Terephthalate (PET) as coarse aggregate replacement and suitability of plastic aggregate in concrete. The effects of natural aggregate and plastic aggregate in shape and behaviour were investigated. Test for slump, rebound hammer, compressive strength, heat absorption and water absorption were carried out to identify the suitability of plastic aggregate replacement. This study focused on the bottle neck of PET as coarse aggregate replacement and compressive behaviour of concrete with PET, varying the percentage of coarse aggregate replacement (10, 20, 30 and 40 vol%). The compressive strength is decreased as the plastic aggregate content is increased compared to conventional aggregate. This study presents an alternative way of recycling PET to reduce solid plastic waste and capacity of landfills.